Antimicrobial peptides play a functional role in bumblebee anti-trypanosome defense - Soni Deshwal; Mallon, Eamonn (bioRxiv, 2014)
Bumblebees, amongst the most important of pollinators, are under enormous population pressures. One of these is disease. The bumblebee and its gut trypanosome Crithidia bombi are one of the fundamental models of ecological immunology. Although there is previous evidence of increased immune gene expression upon Crithidia infection, recent work has focussed on the bumblebee's gut microbiota. Here, by knocking down gene expression using RNAi, we show for the first time that antimicrobial peptides (AMPs) have a functional role in anti-Crithidia defense.